Accuracy comparisons of intra-articular knee injection between the new modified anterolateral Approach and superolateral approach in patients with symptomatic knee osteoarthritis without effusion - Bancha Chernchujit; Suthee Tharakulphan; Adinun Apivatgaroon; Renaldi Prasetia (Elsevier, 2019)
Background: Intra-articular knee injection with steroid or various other agents have been used to control the local inflammation and relieve pain in the osteoarthritis knee. To achieve the maximal potential therapeutic worth and decrease the complications from the inaccurate knee injection, these medications should be delivered directly into the intra-articular space. Injection technique is one of the most important factors for accuracy of knee injection. Therefore, this study was aimed to propose the new modified anterolateral injection technique for higher accuracy of knee injection in symptomatic osteoarthritis knee without effusion. Material and methods: Patients with symptomatic osteoarthritis without effusion were included prospectively from May 2014 to May 2015 and randomized into 2 groups for knee injection: Modified anterolateral (MAL), Standard superolateral (SL). Knee injection was performed by one experienced orthopaedic. Accuracy of injection was test by mini air-arthrography technique. The pain from injection were evaluated by visual analog scale (VAS). Result: 132 knees were included, 66 knees were modified anterolateral group same as superolateral group. The modified anterolateral injection was significantly yield the higher accuracy rate than the standard superolateral injection (89% vs 58%, P < 0.05). The pain visual analog scale was not significantly different between the modified anterolateral and standard superolateral injection technique (2.61 vs 2.65, P = 0.917) No adverse events were occurred. Conclusion: The new modified anterolateral injection yields the higher pooled accuracy rate. From the accuracy and the advantage of the new modified anterolateral injection, this is the preferred injection technique for the symptomatic osteoarthritis without knee effusion. Keywords: Accuracy, Knee injection, Anterolateral, Superolateral, Backflow